PEMBANGUNAN SUMBER DAYA MANUSIA DALAM PERSPEKTIF EKONOMI PENDIDIKAN - Rustina, Rustina (State Institute of Islamic Studies (IAIN) Palu, 2007)
This article discusses the infect of human recourses development in the prospect of education economy. It descriptively analyses education program and its relationship with education economy. To enhance the quality of human resources of a nation, socio-economic factor will determine human resources development. Education will improve if an education institution is able to build network with other institutions, in the context of transparency, socio-economic structure. Kata Kunci: Pembangunan, sumber daya manusia, persfektif ekonomi, Pendidikan